Postoperative Magnesium Sulfate Repletion Decreases Narcotic Use in Abdominal-Based Free Flap Breast Reconstruction - Lu, Yi-Hsueh; Jeon, Jini; Mahajan, Lakshmi; Yan, Yufan; Weichman, Katie E.; Ricci, Joseph A. (Journal of Reconstructive Microsurgery, 2024)
Background Microsurgical breast reconstruction after mastectomy is now the standard of care for breast cancer patients. However, the costs and resources involved in free flap reconstruction can vary across different medical settings. To enhance patient outcomes in a cost-effective manner, we investigated the effect of intravenous magnesium sulfate (IV Mg) on postoperative opioid usage in this context.Methods A retrospective chart review was performed on all consecutive patients who underwent abdominal-based free flap breast reconstruction in a single institute following an enhanced recovery after surgery (ERAS) protocol. Patients who received IV Mg were compared with those who did not receive supplementation. Serum magnesium levels at different time points, narcotic consumption in units of oral morphine milligram equivalents (MMEs), and other postoperative recovery parameters were compared.Results Eighty-two patients were included. Those who received IV Mg on postoperative day 0 (n = 67) showed significantly lower serum magnesium levels before repletion (1.5 vs. 1.7 mg/dL, p = 0.004) and significantly higher levels on postoperative day 1 after repletion (2.2 vs. 1.7 mg/dL, p = 0.0002) compared to patients who received no magnesium repletion (n = 13). While both groups required a similar amount of narcotics on postoperative day 0 (20.2 vs. 13.2 MMEs, p = 0.2), those who received IV Mg needed significantly fewer narcotics for pain control on postoperative day 1 (12.2 MMEs for IV Mg vs. 19.8 MMEs for No Mg, p = 0.03). Recovery parameters, including maximal pain scores, postoperative mobilization, and length of hospital stay, did not significantly differ between the two groups.Conclusion This is the first study to describe the potential analgesic benefits of routine postoperative magnesium repletion in abdominal-based free flap reconstruction. Further research is necessary to fully understand the role of perioperative magnesium supplementation as part of an ERAS protocol.
Keywords: magnesium sulfate; enhanced recovery after surgery (ERAS); autologous breast reconstruction